CRIMINAL PROCEEDINGS AGAINST PRISONERS OF WAR - Holdberh, Natalia; Tsypan, Anzhela (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is to determine the status of a prisoner of war and his rights when involved in investigative (search) actions, as well as the properties of the pre-trial process. Research methods: to achieve a certain goal, general and special scientific methods were used, in particular, dialectical, axiological, objectivity, systemicity, analysis, induction and comparative law. Results: generalized requirements for conducting investigative (search) actions involving prisoners of war in accordance with international law and national law. Discussion: in the process of research, the status of a prisoner of war, his rights depending on participation in investigative actions and the trial are described in detail. Attention is drawn to the number and types of war crimes committed by the military of the Armed Forces of the Russian Federation on the territory of Ukraine. The features of conducting an investigative experiment as an investigative (investigative) action with the participation of Russian prisoners of war in the cities of Ukraine are analyzed. Attention has been paid to the changes made to criminal law after the beginning of a full-scale invasion concerning criminal proceedings against prisoners of war and their exchange. Thus, it is important to study the criminal proceedings against prisoners of war, taking into account the requirements of international legal acts regulating this issue. The peculiarity of the investigative (search) actions described in the article is the status of a prisoner of war, his rights and procedure for treatment enshrined in the Geneva Convention on the Treatment of Prisoners of War. The novelty of scientific work lies in the ratio of general theoeretic international and national norms and the practice of their application in Ukraine. Interrogation plays an important role because it is a source of information about events and circumstances that entailed certain consequences. The investigative experiment helps to recreate the sequence of actions at the scene of the crime, which greatly facilitates its investigation.